2004
DOI: 10.1212/01.wnl.0000147289.50605.dc
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and other headaches

Abstract: The lack of association of migraines with coronary heart disease suggests that the association of migraine with Rose angina is not related to coronary artery disease. Future research assessing other common underlying pathologic mechanisms is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 47 publications
3
80
0
Order By: Relevance
“…Due to the association between migraine (mostly MA) and ischemic stroke, it is of interest whether migraine is similarly associated with coronary heart disease as well. Although some studies yielded negative or conflicting results for overall migraine, 39 case reports 40 and large-scale cohort studies 9 found an association between migraine and chest pain. In some cases, migraine was associated with ischemic electrocardiographic changes.…”
Section: Shared Risk Factors and Shared Co-morbidities: Migraine And mentioning
confidence: 99%
“…Due to the association between migraine (mostly MA) and ischemic stroke, it is of interest whether migraine is similarly associated with coronary heart disease as well. Although some studies yielded negative or conflicting results for overall migraine, 39 case reports 40 and large-scale cohort studies 9 found an association between migraine and chest pain. In some cases, migraine was associated with ischemic electrocardiographic changes.…”
Section: Shared Risk Factors and Shared Co-morbidities: Migraine And mentioning
confidence: 99%
“…Population studies support the relationship between migraine, specially MA, and coronary disease. In the Atherosclerosis Risk in Communities study 37 , patients with headache were roughly twice as likely to have a history of angina, as compared to controls, with the risk most elevated in the headache group with aura.…”
Section: Mechanisms Of Association Putative Mechanisms Commentsmentioning
confidence: 97%
“…Migraine and coronary heart disease Although some studies yielded negative or conflicting results for the overall association of migraine and coronary heart disease 35 , other studies reported a positive association and even electrocardiographic changes experienced by migraineurs [36][37][38] . Population studies support the relationship between migraine, specially MA, and coronary disease.…”
Section: Mechanisms Of Association Putative Mechanisms Commentsmentioning
confidence: 99%
“…In the Atherosclerosis Risk in Communities study 37 , patients with headache were roughly twice as likely to have a history of angina, as compared to controls, with the risk most elevated in the headache group with aura.…”
Section: Mechanisms Of Association Putative Mechanisms Commentsmentioning
confidence: 97%
“…Migraine and coronary heart disease Although some studies yielded negative or conflicting results for the overall association of migraine and coronary heart disease 35 , other studies reported a positive association and even electrocardiographic changes experienced by migraineurs [36][37][38] .…”
Section: Mechanisms Of Association Putative Mechanisms Commentsmentioning
confidence: 99%